Propolis effect on streptozotocin-induced diabetic rats - Sartori, D. R.S. [UNESP]; Kawakami, C. L. [UNESP]; Orsatti, C. L. [UNESP]; Sforcin, José Maurício [UNESP] (FapUNIFESP (SciELO), 2009)
Propolis is one of the hive products that has been used extensively in folk medicine, due to its several biological and pharmacological properties. Besides, propolis-containing products have been intensely marketed by the pharmaceutical industry and health-food stores. This work was carried out in order to investigate whether propolis treatment could revert the metabolic alterations of streptozotocin-induced diabetic rats. Animals were kept in metabolic cages and diabetes was induced by a single dose of streptozotocin (35 mg/kg, IV). After a week, rats with glycemia higher than 230 mg/dL were divided into two groups and treated with ethanolic extract of propolis (10 and 90 mg/kg, PO) for seven days. Glycemia and free fatty acids were determined, as well as food and water intake, body weight and urine volume were registered weekly. Data showed no significant differences in the analyzed variables. Based on these results, one may conclude that propolis had no effects after diabetes establishment, in our conditions assays. Further assays with different concentrations of propolis and periods of administration should be carried out in order to evaluate its therapeutic potential in this disease.
Keywords: Brazilian propolis; Diabetes; Free fatty acids; Glucose